(untitled) - Strobel, Stefan (New York, 1997)
Hailed in previous editions for its user-friendliness, this third edition of Linux Universe contains the newest Linux Kernel 2.0.25 on two fully configured CD-ROMs for easy installation. The new edition contains several powerful new features, including Java SDK (binary), Xemacs, Netatalk (Appletalk connectivity), and IP firewall administration tools.
Keywords: Hệ điều hành (máy tính),Operating systems (Computers)